Establishment of a New Abdominal Aortic Aneurysm Model in Rats by a Retroperitoneal Approach - Zhu, Jun-Xing; Tang, Quan-Qiao; Zhou, Can; Shi, Xing-Chi; Yi, Si-Yi; Yang, Ying (Frontiers in Cardiovascular Medicine, 2022)
Background:Constructing an ideal model of abdominal aortic aneurysm (AAA) is of great significance to elucidate its complex pathogenesis. Therefore, we introduce a new and simple method to simulate human AAA, and construct a rat AAA model through retroperitoneal approach. Methods:Forty healthy adult SD rats were randomly divided into control group, elastase + calcium chloride group (PPE+CaCL2), elastase group (PPE) and elastase + beta aminopropionitrile group (PPE+BAPN) according to the male-female ratio of 1: 1, with 10 rats in each group. Retroperitoneal approach was used to free the infrarenal abdominal aorta in all four groups. In PPE + CaCL2 group, 0.1 ml of elastase (about 5U) was perfused into arterial cavity for 20min, and 1.0 mol/L calcium chloride was infiltrated out of arterial cavity for 10min. In PPE group, 0.1 mL of elastase (about 5U) was perfusion into arterial cavity for 20min, and normal saline was infiltrated out of arterial cavity for 10min; PPE + BAPN group combined with 0.3% BAPN drinking water/day on the basis of PPE group; Control group was treated with saline instead of elastase and calcium chloride.Histopathology, immunohistochemistry, qPCR, WB, gelatin zymogram and other methods were used to study. Result：The operation time of the four groups was controlled at about 40 minutes, and the success rate of operation was 100%.Survival rate: Control Group (100%) = PPE Group (100%) > PPE + CaCL2 Group (90%) > PPE + BAPN Group (40%);Aneurysm formation rate: PPE + BAPN Group (100%) > PPE + CaCL2 Group (80%) > PPE Group (60%) > Control Group (0%);;Inflammatory cells (macrophages, T cells, B cells, dendritic cells) infiltrated in different degrees in PPE + CaCL2, PPE and PPE + BAPN groups; Compared with the control group, the vascular thickness, elastic fiber content, collagen fiber content and vascular smooth muscle cell content in PPE + CaCL 2, PPE and PPE + BNPA groups decreased significantly (P < 0.05), while the expression and activity of MMP2 and MMP9 increased significantly (P < 0.05). Conclusion：A new, simple and reproducible rat abdominal aortic aneurysm model can be constructed by retroperitoneal approach.